2007
DOI: 10.1007/s10549-007-9739-9
|View full text |Cite
|
Sign up to set email alerts
|

Drug metabolism-related genes as potential biomarkers: analysis of expression in normal and tumour breast tissue

Abstract: The complex role of drug metabolism-related enzymes and their possible influence in cancer development, treatment and outcome has not yet been completely elucidated. There is evidence that these enzymes can activate certain environmental procarcinogens to more toxic derivatives and thus a role has been proposed for them in carcinogenesis. The fact that they can also inactivate a number of chemotherapeutic drugs has raised the possibility of these enzymes influencing the sensitivity of tumour cells to anticance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 32 publications
3
23
0
Order By: Relevance
“…Our finding shows that ARNT2 is not a prognostic indicator in both 90A cohort and 181A cohort (III and IV of Figure S5.2). However, its mRNA expression is up-regulated in tumor component, which is consistent with the report [20]. Liu et al [21] reported that ARNT2 dimerizes with SIM1 to up-regulate their downstream target genes (268 probes) in vitro , which are predicted to be functional in seven categories—transcription regulators, signaling components, metabolic enzymes, channels and transporters, cell adhesion and migration, miscellaneous and uncharacterized.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Our finding shows that ARNT2 is not a prognostic indicator in both 90A cohort and 181A cohort (III and IV of Figure S5.2). However, its mRNA expression is up-regulated in tumor component, which is consistent with the report [20]. Liu et al [21] reported that ARNT2 dimerizes with SIM1 to up-regulate their downstream target genes (268 probes) in vitro , which are predicted to be functional in seven categories—transcription regulators, signaling components, metabolic enzymes, channels and transporters, cell adhesion and migration, miscellaneous and uncharacterized.…”
Section: Resultssupporting
confidence: 82%
“…Qin et al [19] reported ARNT2 affecting HIF1 regulatory signaling and metabolism in human breast cancer cell model. It is a potential favorable prognostic factor in breast cancer when it is elevated and it is expressed higher in tumor component than in non-tumor component [20]. Our finding shows that ARNT2 is not a prognostic indicator in both 90A cohort and 181A cohort (III and IV of Figure S5.2).…”
Section: Resultsmentioning
confidence: 68%
“…Extensive evidences have clearly indicated the modulatory role of the ligand-activated Ahr in different types of cancers [2628]. In breast cancer, previous studies have demonstrated that the agonist-activated Ahr modulates invasiveness and metastasis of breast cancer cells, the main causes for tumor recurrence, suggesting Ahr as a promising therapeutic strategy [29, 17, 14, 16].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the metabolism of a drug in cancer cells is of great interest for scientists interested in designing anti-tumor drugs and PK-PD study. Previous studies have shown that the expression levels of many CYP450 isoforms and UDPglucuronosyltransferases (UGTs), glutathione-S-transferases (GSTs), sulfotransferase (SULTs) and sulfatase (SULFs) in hepatoma carcinoma, breast cancer and lung cancer tissues were different from their corresponding normal tissues [17,[35][36][37] . The intracellular NADPH levels [38][39][40] were also different in cancer samples.…”
Section: Drug Metabolism In Cancer Cellsmentioning
confidence: 99%